Some effects of transpiration on the boundary layer at the leading edge of a swept wing - Smith, A. (Cranfield University, 2000)
The effect of transpiration on the boundary layer near the leading edge of a swept wing has been investigated using a large swept cylinder model with a laser-drilled titanium leading edge to model the leading edge of a swept wing. In the region near the leading edge, boundary layer transition due to crossflow instability has been examined. Natural transition on a porous surface was compared with that on a non-porous surface, and it was found that transition occurred at lower R ’s on the porous surface (ie there was a performance penalty due to the porous surface). The effect of suction on transition due to crossflow instability was then studied. It was found that only moderate amounts of suction were required to delay the onset of crossflow-induced transition and a simple algebraic model has been derived, in terms of R , Rex, and Cq, to describe transition on the porous surface with or without suction. It was also found that two-dimensional trip wires had a negligible effect on crossflow transition, except where they caused attachment-line contamination. On the attachment-line, several subjects were addressed. The effect of attachment-line blowing was considered, and good agreement was obtained with previous work. The effect of spanwise blowing length was also addressed, and a simple algebraic model was derived, in terms of R , s/rj, and Cq, to describe attachment-line transition due to blowing. A comparison has also been made with linear stability theory. The effect of suction at the wing-fiiselage junction was examined as an alternative to suction on the attachment-line. However, it was found that applying suction on the attachment-line when the boundary layer had attained infinite swept conditions was much more efficient than applying suction in the junction region. Suction was successfully used to relaminarise a turbulent attachment-line at R values between 600 and 950, the magnitude predicted for the next generation of large transport aircraft. During the experiments, no sign of critical oversuction was found. Finally, the behaviour of a relaminarised attachment-line flowing onto a non-porous surface was studied. The conditions for natural transition on the non-porous surface were measured, and it was found that they were the same as those predicted by previous work on an entirely non-porous attachment-line.